Diabetic foot infections: what have we learned in the last 30 years?. (November 2015) - Uçkay, Ilker; Aragón-Sánchez, Javier; Lew, Daniel; Lipsky, Benjamin A.
Highlights: Diabetic foot infections are a common, complex, and costly problem that will almost certainly increase in prevalence in the near future. Clinical research over the past three decades has markedly increased our understanding of the pathophysiology, diagnosis, and treatment of both soft tissue and bone infections. Diabetic foot infections are a heterogeneous group of infections in a diverse patient population. Therefore it is difficult to determine one optimal management and one optimal duration of antibiotic administration for the entire patient population. The task is to implement available guidelines, to audit processes and outcomes, to educate providers and patients, and to further advance research. Summary: Background: Infection is a common epiphenomenon of advanced diabetic foot disease and the most common reason for diabetes-related hospitalizations and lower extremity amputations. Major advances have been made in the past three decades in our understanding and management of diabetic foot infections (DFIs). The optimal treatment of DFIs clearly involves multidisciplinary input. Methods: A comprehensive search of the literature on DFIs from January 1960 through June 2015 was performed, with an emphasis on information published in the past 30 years. Results: There have been many new insights into the microbiology, diagnosis, and treatment of DFIs, although the implementation of this knowledge in clinical practice has been suboptimal. Today, the use of evidence-based guidelines, multidisciplinary teams, and institution-specific clinical pathways helps guide optimal care of this multifaceted problem. Patients are more often treated in the ambulatory setting, with antibiotic regimens that are more targeted, oral and shorter course, and with more conservative (but earlier) surgical interventions. New diagnostic and therapeutic methods are being developed at an accelerating pace. Conclusions: The worldwide increase in the incidence of diabetes and longer lifespan of diabetic patients will undoubtedly increase the incidence of DFIs. Clinicians caring for diabetic patients should have an understanding of current methods for preventing, diagnosing, and treating DFIs.